(untitled) (Journal of Mathematics Mechanics and Computer Science, 2018)
Information and communication technologies are widely used for solving actual problems, faced by modern science. The goal of the current paper is to justify the need for and prepare recommendations for requirements of a geoinformatical system (GIS) for gathering, processing, and visualization of experimental geophysical ground and satellite data for the periods of seismic activity on Northern Tian Shan. We recommend to create a geoinformatical system, based on modern technologies, and using experimental data, mathematical modelling, and computing technologies. We recommend to organize access to necessary resources in the common geoinformation space: satellite measurements of interplanetary magnetic field (velocity, temperature, density, concentration of streams of solar wind particles); GPS-measurements; Ground-based measurements of geomagnetic field parameters, and International and Kazakhstani seismological catalogs. We recommend to realize a graphical presentation of data for specific seismic event in the demanded time interval with help of computer software and portlets (internal support programs). The created GIS will allow to analyze effects in geophysical fields for specific seismic events in region of Northern Tian Shan on pre-earthquake stages and during the earthquake.